Mengeksploitasi Keterlibatan Anak Penjual Aksesoris di Kawasan Wisata Desa Kuta Mandalaka - Lalu Muazim (Journal of Mandalika Literature, 2025)
The rapid development of tourism in Central Lombok has made this area one of the national priority tourist destinations. The diversity of tourist destinations and their natural beauty, especially exotic beaches, has attracted world attention, making this region a great potential in the international tourism industry. Tourism development in central Lombok, especially in the kuta mandalika beach area, does have a positive impact on the economy, especially in increasing investment, opening up jobs, and empowering local communities. However, on the other hand, a number of social problems have emerged, one of which is the issue of child labor. This research is motivated by the phenomenon of school-age child labor as an accessory seller at Kuta Mandalika Beach. Child labor in the tourism sector is not just a phenomenon where children work and receive wages, but a more complex problem that touches on aspects of exploitation, hazardous working conditions, and extensive negative impacts on children's lives. This study aims to determine the causal factors and impacts of exploitation of school-age children as accessories traders at Kuta beach, using qualitative methods through a phenomenological perspective. Subjects in this study were collected using purposive sampling method. Data collection techniques used observation, interview and documentation techniques. After analyzing all the data collected, child exploitation that occurs in the kuta mandalika village tourist area is caused by economic factors, high education costs, self and environmental encouragement, and parental support. The impact of child exploitation as an accessories trader is closely related to the obstruction of access to education and hampering the physical, psychological, and social development of children.